Esther and the king. - Agle, Kenneth; Schaertl, Micahel L.; Agle, Dennis; Edson, Aaron; Smart, Summer Naomi ([Provo, Utah] : Lightstone Pictures, 2010)
When a modern-day girl named Amelia faces a big challenge in her life, her mother teaches her about the power of fasting by sharing the story of a heroine in the Bible (Esther 2-8)
Title from container
Originally released by Lightstone Productions in 2006
Bonus features: "Building character" featurette; "Fly-on-the-wall" featurettes; Gag reel; Audio Commentary; English and Spanish subtitles
Keywords: Esther, Queen of Persia -- Juvenile films; Bible -- Esther -- Juvenile films; Bible stories, English -- Esther -- Juvenile films